Rising powers, global capitalism and liberal global governance: A historical materialist account of the BRICs challenge - Matthew D. Stephen (European Journal of International Relations, 2014)
This article analyses the phenomenon of rising powers from a historical materialist perspective. It (1) elaborates the key concepts of historical structures of world order, state–society complexes and transnational class formation, and (2) applies them to Brazil, Russia, India, China and other so-called `rising powers' to account for the nature and extent of the challenge they pose to the existing institutions of global governance. A double argument is advanced: first, the integration of rising powers into the historical structure of global capitalism has reduced traditional sources of great power conflict, and made rising powers heavily dependent on the existing institutional framework established by the liberal West. This facilitates their integration into the existing governance order. However, within the limits of the existing order, two factors lend a heartland–contender cleavage to the politics of global governance: the rising powers' relatively more statist, less market-driven forms of state, and their subsequent failure to be integrated into emergent transnational capitalist class structures. Consequently, it is not the global governance order itself, but its most liberal features, that are contested by rising powers. The result is that, in contrast to realist pessimism and liberal optimism, the rise of new powers is leading to a hybrid governance order that is both transnationally integrated and less liberal.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330; economic interdependence; global institutions; globalization; Marxism; multipolarity; political economy